Basket anode filled with CaCO3 particles: A membrane-free electrochemical system for boosting phosphate recovery and product purity. (1st March 2023) - Zhan, Zhengshuo; Wang, Runhua; Saakes, Michel; van der Weijden, Renata D.; Buisman, Cees J.N.; Lei, Yang
Highlights: Basket anode with CaCO3 packing derives acidic and alkaline regions as membranes. The system realizes enhanced P recovery and boosted product purity. Nearly 100% of the recovered P ends up at cathode as high-purity Ca-phosphate. The applied current, packing material's size, and influent P level are critical. Basket-anode system shows high stability and capability in treating real urine. Abstract: Phosphorus (P) is often regarded as the primary stimulant for eutrophication, while its importance as a crucial life element is also well acknowledged. Given its future scarcity, P recycling from waste streams is suggested and practiced. Electrochemically mediated precipitation (EMP) is a robust and chemical-free process for P removal and recovery, yet it requires further developments. The first generation of the CaCO3 -packed electrochemical precipitation column successfully solved the problem of H + -OH − recombination, achieving enhanced P removal efficiency with less energy consumption but suffering from low Ca-phosphate purity in recovered products. Herein, a new concept of a basket-anode electrochemical system is proposed and validated to prevent direct H + -OH − recombination and enhance product purity. The CaCO3 pellets packed basket anode alleviates the OH − depletion by CaCO3 -H + interaction and provides extra Ca 2+ for enhanced P removal. The novel structure of the basket anode, by its derived acidic anode region and alkaline cathode region, completely avoids the precipitation of Ca-phosphate on the packed CaCO3 and greatly facilitates the collection of high-quality Ca-phosphate product. Our results suggest that almost 100% of the removed P was in high-purity, highly crystalline Ca-phosphate on the cathode. The recovered products contained significantly more P (13.5 wt%) than in the previous study (0.1 wt%) at similar energy consumptions (29.8 kWh/kg P). The applied current density, pellets size, and influent P concentration were critical for P removal performance, product purity, and power consumption. We further demonstrated the long-term stability of this novel system and its technical and economic feasibility in treating real stored urine. Our study provides new cell architectural designs to enhance the performance of EMP systems and may inspire innovations and developments in other electrochemical water treatment processes. Graphical abstract: Image, graphical abstract